Evaluation of the Reinforcement Performance of Loess Slopes Affected by Rainfall Infiltration - Yongdong Yang; Hai Liu; Hongfei Li; Shengrui Su; Wanfeng Liu; Yunxiu Dong; Dong Wang (Geofluids)
The instability disaster of slope engineering is the third largest geological disaster after earthquake and debris flow, and rainfall is an important factor affecting the stability of slopes. In this study, the stability of a loess slope affected by rainfall infiltration was investigated using engineering examples, an in-depth site investigation, geotechnical physical and mechanical tests, and numerical simulations. The finite element software ABAQUS was used to establish a model of the rainfall infiltration slope to analyze the slope stability after rainfall infiltration while considering the influence of the groundwater level on slope stability and evaluated the reinforcement performance of retaining wall and biological measures on loess slope under rainfall conditions. The results showed that the displacement and pore pressure at the bottom of the slope increased after a strong rainfall. The rapid rise of the water level caused increases in the displacement and pore pressure of the slope, but the slope stability improved when the water table reached 0.8 m. Further analysis shows that under the joint action of rainfall and groundwater, the slope stability can be effectively improved by using retaining wall to strengthen the slope. Under the action of rainfall, the increase of vegetation depth and density has a certain effect on the improvement of slope stability. The ryegrass and alfalfa were the most effective slope stabilization approach if the vegetation parameters and economic factors were considered.